Hypertension and Headache: the Effect of Antihypertensive Drugs - V. A. Parfenov; T. M. Ostroumova; O. D. Ostroumova (Рациональная фармакотерапия в кардиологии, 2019)
Headache is considered to be one of the main symptoms of arterial hypertension (HT). Complaints of headache are presented by many patients with HT: from 44% to 87%. It is obvious that the majority of complaints of headache in patients with HT is not due to headaches due to increased blood pressure (BP), but multimorbidity (polymorbidity) – the presence of coexisting primary headaches, most often, as in the population as a whole, chronic tension headache (57-85%) and migraine (15-30%). On the other hand, the frequency of HT in patients with migraine ranges from 32% to 44%. The relationship between migraine and HT may be due to common exogenous (external) and endogenous (genetic) factors, as well as common pathophysiological mechanisms. External risk factors, which can be associated with both migraine and HT, include the nature of the diet (excessive consumption of table salt with food), low physical activity, chronic stress; both diseases are also associated with the presence of a connection with the metabolic syndrome. The role of hyperactivation of the renin-angiotensin-aldosterone and adrenergic system and endothelial dysfunction are actively discussed. Angiotensin-converting enzyme takes an active part in the BP control and vascular tone; it is known that some angiotensin converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) have demonstrated efficacy in preventing migraine attacks. The presence of HT can contribute to the chronic course of primary headache, and effective treatment of HT with antihypertensive drugs, on the contrary, can have a positive effect on the course of primary headaches. Antihypertensive drugs reduce the frequency of headaches compared to placebo, but heterogeneity between different classes was revealed. There was a statistically significant decrease in the frequency of headaches compared to placebo during treatment with beta-blockers, ACEI, ARB, diuretics, while calcium antagonists did not reduce the frequency of headaches. According to a number of studies, the frequency of headaches during the treatment with ARB (candesartan) is comparable to that in the placebo group. Some antihypertensive drugs are used to prevent migraine attacks.